2002
DOI: 10.1007/s101950200018
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous elastic fixation of proximal humeral fractures: operative indications, techniques, results and complications

Abstract: IntroductionFractures of the proximal humerus represent 4%-5% of all fractures. Although they can occur anytime after birth, their incidence increases progressively with age, particularly in women, because of postmenopausal osteoporosis, so that about 80% of affected people older than 50 years are women [1].The most used classification of these fractures was developed by Neer [2] in 1970 ( Fig. 1), starting from Codman's classification, based on the four constitutive fragments of the proximal humerus (head, tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Many operative techniques and fixation methods have been used to treat displaced proximal humeral fractures [2,4,6,8,9,11,13,14,16,19,20,21]. Current trends in surgical technique for four-part "valgus impacted" fractures include limiting soft tissue dissection around the fracture fragments, reduction of the head to its anatomical position, and minimally invasive osteosynthesis [10,12,[17][18][19]22].…”
Section: Discussionmentioning
confidence: 99%
“…Many operative techniques and fixation methods have been used to treat displaced proximal humeral fractures [2,4,6,8,9,11,13,14,16,19,20,21]. Current trends in surgical technique for four-part "valgus impacted" fractures include limiting soft tissue dissection around the fracture fragments, reduction of the head to its anatomical position, and minimally invasive osteosynthesis [10,12,[17][18][19]22].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study are comparable with the results of Fenichel et al [11] using threaded pins for two-part fractures as they achieved an average Constant score of 86 points (range 78-100 points) and also for the range of motion. Rosa et al [12] reported a Constant score between 33 and 84 points using two elastic smooth pins inserted through the head at the level of the physis. The common complications reported in the literature are pin site infection, stiffness, loss of fixation, axillary nerve injury, secondary displacement, and deep infection [13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Rosa et al [12] reported a Constant score between 33 and 84 points using two elastic smooth pins inserted through the head at the level of the physis. The common complications reported in the literature are pin site infection, stiffness, loss of fixation, axillary nerve injury, secondary displacement, and deep infection [13][14][15] . In the present study, We had total 3 complications include 1 pin site infection; 5 post traumatic stiffness & 1 case of avascular necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical options include different fixation techniques (percutaneous pinning, intramedullary nailing, plating) as well as shoulder arthroplasty. 6 The choice of procedure should be made considering several local( fracture pattern, quality of bone, status of rotator cuff) and general (comorbidities, functional demands, compliance to treatment) factors. Unfortunately, insufficient straightforward recommendations and significant variation in clinical practice among orthopaedic surgeons indicates a lack of consensus regarding optimal treatment of these fractures.…”
Section: Introductionmentioning
confidence: 99%